The Exploration Significance of Ag/Au, Au/Cu, Cu/Mo, (Ag×Au)/(Cu×Mo) Ratios, Supra-ore and Sub-ore Halos and Fluid Inclusions in Porphyry Deposits: A Review - H. Atapour (Journal of Sciences, Islamic Republic of Iran)
This paper documents the exploration significance of Ag/Au, Au/Cu, Cu/Mo and (Ag×Au)/Cu×Mo) ratios of the supra-ore and sub-ore halos versus fluid inclusion evolution for 24 Cu, 6 Cu- Mo and 10 Cu-Au porphyry deposits worldwide. The ratios are based only on the economic and mineralized hypogene alteration zones. The results indicate that (Ag×Au)/(Cu×Mo), Au/Cu and Cu/Mo ratios increase with decreasing depth and could be considered as the possible exploration guides for many as-yet- undiscovered unexposed porphyry deposits. These ratios are well correlated with vertical elemental vector zoning and alteration halos from the center (proximal potassic) outward (distal propylitic-zeolitic) and follow the order of Cu-Mo-Au, Cu-Zn, Zn-Pb-Ag, Ag-Pb- As-Sb-Hg-Au. On the basis of the (Ag×Au)/(Cu×Mo) ratios and fluid inclusion data, the Iranian continental arc porphyry copper deposits show multiphase halite-sylvite saturated fluid inclusions and formed between 2 to 4.75 km depth. The simple and multiple geochemical ratios and fluid inclusion evolution highlight that the Cu, Cu-Mo and Cu-Au porphyry deposits of the world were probably formed at <8-0.6,